2015
DOI: 10.1038/srep11899
|View full text |Cite
|
Sign up to set email alerts
|

Cortical dynamics and subcortical signatures of motor-language coupling in Parkinson’s disease

Abstract: Impairments of action language have been documented in early stage Parkinson’s disease (EPD). The action-sentence compatibility effect (ACE) paradigm has revealed that EPD involves deficits to integrate action-verb processing and ongoing motor actions. Recent studies suggest that an abolished ACE in EPD reflects a cortico-subcortical disruption, and recent neurocognitive models highlight the role of the basal ganglia (BG) in motor-language coupling. Building on such breakthroughs, we report the first explorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 59 publications
1
77
0
3
Order By: Relevance
“…Other clinical evidence sustaining the causal link between language processing and the motor systems comes from studies on Parkinson’s patients (e.g., Cardona et al, 2014; Melloni et al, 2015) exploiting the so-called action-sentence compatibility effect (ACE, Glenberg and Kaschak, 2002). This effect shows that comprehending a sentence describing an action denoting movements toward or away from the body (e.g., ‘Launch the ball’ or ‘Close the drawer’) facilitates movements in the same direction, but slows down movements in the opposite direction.…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical evidence sustaining the causal link between language processing and the motor systems comes from studies on Parkinson’s patients (e.g., Cardona et al, 2014; Melloni et al, 2015) exploiting the so-called action-sentence compatibility effect (ACE, Glenberg and Kaschak, 2002). This effect shows that comprehending a sentence describing an action denoting movements toward or away from the body (e.g., ‘Launch the ball’ or ‘Close the drawer’) facilitates movements in the same direction, but slows down movements in the opposite direction.…”
Section: Discussionmentioning
confidence: 99%
“…These steps are critical and perhaps unavoidable to characterize the organ's functional organization with some degree of external validity. Indeed, thanks to this approach, replicable associations have been established between damage to circumscribed regions and impairments of specific functions, including motor (Zgaljardic et al, 2003), somatosensory (Meyer et al, 2016), socio-cognitive (Gold and Shadlen, 2007; Ibáñez et al, 2010, 2016b; Couto et al, 2013; Baez et al, 2014, 2016b,c; Melloni et al, 2016), interoceptive (Couto et al, 2015; García-Cordero et al, 2016), executive (Rabinovici et al, 2015; Sedeño et al, 2016), linguistic (Ullman, 2008; Cardona et al, 2014; García and Ibáñez, 2014, 2016; Bocanegra et al, 2015; García, 2015; Melloni et al, 2015; García et al, 2016a,b,c; Abrevaya et al, 2017), and pragmatic (Kaplan et al, 1990; Stemmer, 2008) skills.…”
Section: Introductionmentioning
confidence: 99%
“…(2014) found that the action-sentence compatibility effect (ACE) was abolished in early PD patients, but not in patients with peripheral motor deficits. The lack of an ACE effect in PD has been shown to be due to reduced motor potential, aberrant frontotemporal connectivity, and overall volume of basal ganglia atrophy (Melloni et al, 2015). Action language deficits have also been observed in language production: Bocanegra et al (2015) found disruptions of action verb production in PD patients compared to controls.…”
mentioning
confidence: 99%